New insights into SUMOylation and NEDDylation in fibrosis - Han, Jin; Wu, Jun; Kou, Wen-Tao; Xie, Li-Na; Tang, Ya-Li; Zhi, Da-Long; Li, Ping; Chen, Dan-Qian (Frontiers in Pharmacology, 2024)
Fibrosis is the outcome of abnormal tissue repair process that the normal tissue is replaced by scar tissue, and causes persistent tissue damage and cellular injury. During fibrosis process, many cytokines and chemokines is involved, and their activity is controlled by post-translational modifications, especially SUMOylation and NEDDylation. Both SUMOylation and NEDDylation have the three-step process that consists of activation, conjugation and ligation, and three kinds of enzymes are involved, including E1 activating enzyme, E2 conjugating enzyme and E3 ligase enzyme. SUMOylation participate organ fibrosis through modulating FXR, PML, TGF-β receptor I, Sirt3, HIF-1α and Sirt1, and NEDDylation influences organ fibrosis through regulating cullin3, NIK, SRSF3 and UBE2M.Further investigations exhibit the therapeutic potential of SUMOylation /NEDDylation activators and inhibitors against organ fibrosis, especially ginkgolic acid in SUMOylation and MLN4924 in NEDDylation. These results demonstrate the therapeutic effect of SUMOylation and NEDDylation against organ fibrosis, and highlight their activators and inhibitors as potential candidates. In the future, the deep investigation of SUMOylation and NEDDylation are urgent to identify novel substrates against organ fibrosis, and the clinical investigation are needed to determine the therapeutic effect of their activators and inhibitors to benefit patients. The information in this review highlights that SUMOylation and NEDDylation functions as the potential therapeutic target for organ fibrosis.